The Influence of Financial Performance, Capital Structure, and Debt Policy, on Company Value With Company Size as Amoderation Variable - Sofiyana, Sofiyana; Santoso, Suryo Budi; Amir, Amir; Santoso, Selamet Eko Budi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
Company value reflects investors' views of a company and is generally associated with the share price and profits earned. Financial performance, capital structure, and debt policy can all influence the rise and fall of a company's value. The aim of this research is to see whether financial performance, capital structure and debt policy influence company value, with company size as a moderating variable. The population of interest in this research are companies listed on the Jakarta Islamic Index (JII70) between 2020 and 2022. The data collection method used is exhaustive sampling or often called saturated sampling, where the entire population of companies in JII70 is used as the research sample. The results of the research show that financial performance has a positive effect on company value, capital structure has a negative effect on company value, debt policy and company size have no effect on company value, company size moderates capital structure on company value, and company size does not moderate financial performance and debt policy on company value.